Modern Primitives : Race and Language in Gertrude Stein, Ernest Hemingway, and Zora Neale Hurston. - Pavloska, Susanna (Literary criticism and cultural theory., 2014)
First Published in 2000. Routledge is an imprint of Taylor & Francis, an informa company.